Peningkatan Kualitas Proses dan Hasil Belajar Biologi Materi Mutasi Melalui Strategi Pemetaan Konsep Siswa Kelas XII IPA 6 SMA Negeri 7 Makassar - Hajar, Abdul (Universitas Negeri Makassar, 2018)
Abstract. The author's experience in teaching material all this time shows that most students feel boredom in their learning, students are still less active in asking questions and responding to learning, students only listen to the teacher's explanation. So, it needs to be given an effective way of learning. There needs to be an effort to introduce a way to help students learn to master concepts and are interrelated so that they can learn meaningfully. One alternative that can meet expectations is the use of concept mapping strategies, especially strategies in the teaching and learning process on mutation material, which is given to students of class XII IPA 6 even semester 2015. This research was carried out in 2 cycles, each cycle consisting of: planning, implementation, observation and evaluation and reflection. The results showed that the use of concept mapping strategies in the learning process can improve the process and learning outcomes of students in learning biology in the mutation material of students of class XII IPA-6 Makassar Senior High School 7. Student learning achievement obtained from the first cycle to the second cycle is the highest value achieved is 85 and 95. The average score from the first cycle to the second cycle is 71.74 and 85. Student responses to learning using concept mapping strategies can increase student learning motivation , facilitate learning for students, can attract students 'attention to learning, increase the quality of learning and can increase students' interest in learning. Keywords: Process Quality, Learning Outcomes, Concept Mapping Strategies, and Mutations.